TRANSFORMATION OF PERFORMANCE EVALUATION PROCESS IN THE DIGITAL ERA: A QUALITATIVE STUDY ON THE USE OF TECHNOLOGY AS A PERFORMANCE ASSESSMENT IN IMPROVING TEAM WORK RESULTS - Yudi Irwansyah; Aldwin Surya; Sarah Imelda; Najwa Haura Lahya; Fazhira Azara (International Conference on Health Science, Green Economics, Educational Review and Technology, 2023)
This study aims to examineTransformation of Performance Evaluation Process in the Digital Era: A Qualitative Study on the Use of Technology as a Performance Assessment in Improving Team Work Results. The qualitative research method used in this study provides an in-depth approach to understanding the use of technology as a performance assessment tool. Referring to the views of experts in 2020, this study uses interviews, observations, and document analysis to explore the impact of digital transformation on team work results. The systematic analysis process and compliance with research ethics are expected to produce valid and relevant findings. Transforming the performance appraisal process using technology is an important step for organizations to improve team performance and achieve long-term goals. Although the challenges in its implementation are quite large, with the right strategy and commitment from all parties, technology can bring significant changes in the way organizations conduct performance appraisals, improve the quality and effectiveness of team performance, and optimize the results achieved. The success of this transformation depends on effective change management, wise use of data, and the implementation of policies that prioritize data security and privacy.